Intimations of global law - Walker, Neil (Global law series, 2014)
"This is a book about how we might fruitfully think about global law. Few terms are more topical in the transnational legal literature. Yet there has been little serious discussion - and little agreement where there has been discussion - on what is meant by 'global law', if, indeed, it means anything of note at all. In what follows, I suggest that we can nonetheless arrive at a core sense of global law as an emergent idea and practice"--